Electron paramagnetic resonance spectroscopic studies of iron and copper proteins. Issue 1 (2003) - Taiwo Taiwo, Fatai A. Fatai A.
Abstract : Transition metal (d-group) ions are widespread in nature, essential for structural characteristics and mechanistic specificity of many proteins. Iron and copper are the two most prevalent metals in proteins responsible for the storage and transport of molecules, ions, and electrons. Electron paramagnetic resonance (EPR) spectroscopy has been extensively used for the determination of these metal ions without extensive disruption of the native protein moiety. It also detects variations in coordination geometry due to ligand substitutions as well as multiple valencies of the same metal. This review highlights the unique application of EPR spectroscopy to the study of iron and copper in biological systems. Mention is made of a select number of other metalloproteins.